HISTOCHEMICAL EXAMINATION OF THE SMALL INTESTINAL AFTER LOCAL AND GENERAL ANESTHESIA (ZAMONAVIY TARAQQIYOT VA FAN: 21-ASR YONDASHUVLARI, 2026)
When studying the results of histochemical examination of the small intestine after local and general anesthesia, it was found that both types of anesthesia led to fibrosis in the tissues of the jejunum, duodenum and ileum. In local anesthesia, this process occurred mainly against the background of inflammation and immune response, while in general anesthesia it was associated with ischemic and hypoxic factors. The fibrosis process increased with age, and the amount and distribution of fibrous tissue in 9-month-old rats was significantly higher than in 3-month-old rats.
Keywords: local anesthesia, general anesthesia, rat, histochemical examination.